Rafael Sixto Casado García de Alayeto: Pedagogo del siglo - Valero Blanco, Mirtha María (Transformación, 2024)
Objective: This article aims as at appreciating the significance of Rafael Sixto Casado contribution to education and society at San Anacleto School in socio-historical context of the second half of the 19th century and its impact on social progress. Methods: The author relies on documentary analysis by reviewing the collections of "José Martí" National Library, the National Archive, the Museum of Education and other institutions. A survey given to teachers and students completed the such collection. Results: Rafael Sixto Casado’s pedagogical ideas is preserved in books and other papers of his own. He worked as a teacher and school principal, wrote several school textbooks used along the country and devised the San Anacleto School curriculum. The students he mentored soon become relevant representative of culture and politics in Cuba. Conclusions: The pedagogical work of Rafael Sixto Casado at San Anacleto School represented the continuity of José de la Luz y Caballero pedagogical tradition